KUALITAS PELAYANAN DATA KESEJAHTERAAN PEGAWAI BADAN KEPEGAWAIAN DAERAH KABUPATEN MADIUN - Widanang Sasmito Aji; Herning Suryo Sardjono; Suwardi . (JI@P, 2022)
Service Quality of Employee Welfare Data This study aims to analyze the servicequality of Employee Welfare data. Service quality can be measured from 5dimensions, namely: Tangibility, Reliability, Responsiviness, Assurance, andEmpathy. The sample is determined by probability sampling with a simple randomsampling technique as much as 10% of the average people who apply foremployee welfare every day, namely 8 people, for 6 working days as many as 48people. Data were analyzed descriptively quantitatively with the help oftabulation tables. The results showed that the first tangible dimension showed thehighest percentage of service was having a comfortable waiting room foremployees and meeting the needs for service. The two dimensions of reliabilityare the costs incurred are reasonable and according to the rules, the threedimensions of responsiveness, the highest percentage of service quality is thespeed of employees in providing services, the four dimensions of assurance withthe highest percentage are guarantees of no financing/payment fees, the fifthdimension of empathy is the highest percentage namely the sincerity of employeesin providing services to regional employees in accessing welfare services foremployeesKeywords: Service quality, tangible, reliability, responsiveness, assurance,empathy